The fifth assassin - Meltzer, Brad. (New York : Grand Central Publishing, 2013)
Archivist Beecher White discovers a connection that may link the individuals responsible for the only four successful assassinations of American Presidents after discovering a modern-day killer who is recreating the assassins' crimes.
Keywords: United States. -- National Archives and Records Administration -- Fiction; Archivists -- Fiction; Presidents -- United States -- Assassination -- Fiction; Assassins -- Fiction; Clergy -- Crimes against -- Fiction; Large type books; Washington (D.C.) -- Fiction; Political fiction